Met at the met a Christian ivory pyxis rediscovered in New York - Campini, Ruben 1995- (2023)
Parallel to the evolution of art history as a discrete discipline during the 1800s and 1900s, the rediscovery of medieval ivories is closely linked to their progression from their origins, to private collections, to public spaces in museums. Although the dynamics of the art market today still often lead newfound objects to private, sometimes untraceable, places, other items have followed opposite paths – as in the case of two fragments of a Late Antique ivory pyxis considered here. These fragments, recently put on display at New York’s Metropolitan Museum of Art, entered the collection only in 2020, having made their way through generations of the family of art collector and dealer Dikran Kelekian (1867–1951). This study, the first to be devoted to these fascinating fragments, examines their iconography and tries to trace their provenance, dating, and function.
Keywords: Metropolitan Museum of Art; Geschichte 400-600; Pyxis; Elfenbeinschnitzerei; Elfenbeinrelief; Eucharistie -- Motiv; Ikonographie; Sammlung